The war and democracy / by R.W. Seton-Watson, J. Dover Wilson, Alfred D. Zimmern and Arthur Greenwood - Seton-Watson, R. W. ((Robert William)) Wilson, John Dover (1881-1969) Zimmern, Alfred EckhardGreenwood, Arthur (1880-1954)
Mapa de las fronteral raciales y nacionales de Europa Central | Biblografía. Índice